Effectiveness of clinical pathway for upper respiratory tract infections in emergency department - Bahar Madran; Şiran Keske; Soner Uzun; Tolga Taymaz; Emine Bakır; İsmail Bozkurt; Önder Ergönül (International Journal of Infectious Diseases, 2019)
Objective: We aimed to demonstrate the benefits of implementing a clinical pathway to decrease the inappropriate use of antibiotics in upper respiratory tract infections (URTI) in an emergency department (ED). Methods: The study was performed in a hospital with 300 beds. All patients who applied with URTI from 1st to 30th of April 2017 were included and the appropriateness of the antibiotics were compared with the patients in the same period in 2016. A checklist for the clinical pathway of URTI was completed by the ED physicians. Results: 351 patients were included, 176 these patients were in pre-ASP period and 175 patients were in post-ASP period. The rate of prescriptions including antibiotics was 49% in pre-ASP period and has decreased to 29% in post-ASP period (p < 0.001). Adherence to clinical pathway has increased from 50% to 80% (p < 0.001). In the post-ASP period, clinical pathway was used in 133 out of 175 patients (76%) and the consequently rate of appropriate antibiotic use was 82%. Conclusion: The implementation of clinical pathway for URTI has decreased inappropriate antibiotic use in ED. As the secondary effect, using clinical pathway in ED also has increased the awareness of ED physicians who did not adhere to clinical pathway. Keywords: Antibiotic stewardship, Antibiotic consumption, Clinical pathway, Upper respiratory tract infection